Manfaat Irigasi Hangat Durante Operasi Terhadap Pencegahan Hipotermi Pasca Bedah TUR Prostat - Kusnanto Kusnanto; Harmayetty Harmayetty; Nancy M. Rehatta; Sabilal Alif; Joni Haryanto; Slamet Mustofa (Universitas Airlangga, 2007)
Introduction: Trans Urethral Resection Prostate (TURP) is endourology surgery with used electrical power or with laser power. The objective of this study was to analyze the effect of warm irrigation during operation to prevent hypothermi post operation TURP at the Dr. Soetomo Central Hospital of Surabaya.Methods: A quasy experimental, pre and post-test control group non-randomized design was used in this study. The independent variable was warm irrigation, and the dependent variable was hypothermi. Fourteen sample enrolled by using non-probability purposive sampling. Data were analyzed by using Paired T test with significance level of p < 0.05.Results :The result showed that warm irrigation admitted during operation had effect to the increase body temperature (p=0.000), blood pressure (p=0.000), pulse (p=0.010), respiration (p=0.002), oxygen saturation (p=0.002). Conclusion: warm irrigation is effective to increase body temperature patient with Trans Urethral Resection Prostate (TURP).The Decrease of Anxiety in Secsio Sesaria Mother with